2012
DOI: 10.1111/cns.12040
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells: Therapeutic Perspective for Ischemic Stroke

Abstract: SUMMARY Endothelial progenitor cells (EPCs), which can be cultured in vitro from mononuclear cells in peripheral blood or bone marrow, express both hematopoietic stem cell and endothelial cell markers on their surface. They are believed to participate in endothelial repair and postnatal angiogenesis due to their abilities of differentiating into endothelial cells and secreting protective cytokines and growth factors. Mounting evidence suggests that circulating EPCs are reduced and dysfunctional in various dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 141 publications
(205 reference statements)
2
97
0
Order By: Relevance
“…35 Stromal derived factor 1a (SDF-1a/ CXCL12)/CXCR4 has been extensively illustrated in the recruitment and homing of EPCs to contribute to neovascularization of tumor or ischemic tissue. [39][40][41] Besides, other subtypes of CXC chemokines, such as CXCL1 and CXCL2, also show their important roles in EPCs recruitment. As previous studies have been revealed that CXCL1/ CXCR2 takes an important place in the recruitment of EPCs to the sites of artery injury and lung diseases, we speculated that CXCL1 may also contribute to EPCs homing to gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…35 Stromal derived factor 1a (SDF-1a/ CXCL12)/CXCR4 has been extensively illustrated in the recruitment and homing of EPCs to contribute to neovascularization of tumor or ischemic tissue. [39][40][41] Besides, other subtypes of CXC chemokines, such as CXCL1 and CXCL2, also show their important roles in EPCs recruitment. As previous studies have been revealed that CXCL1/ CXCR2 takes an important place in the recruitment of EPCs to the sites of artery injury and lung diseases, we speculated that CXCL1 may also contribute to EPCs homing to gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EPCs can secret various angiogenic growth factors to promote angiogenesis [5, 6]. Thus, local angiogenesis in the ischemic brain was assessed at 3 days after cerebral ischemia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic cold exposure can recruit BAT, increase energy expenditure, and thereby contribute to body fat reduction in humans [1, 2]. Moreover, energy metabolism disorders (e.g., obesity, diabetes) are associated with the impairment of endothelial progenitor cells (EPCs) and EPC-mediated ischemic angiogenesis; thus, they are important risk factors of cardiovascular and cerebrovascular diseases including stroke [3-5]. EPCs, a circulating bone marrow (BM)– derived cell population that participates in vasculogenesis and vascular homeostasis, have been used to successfully improve functional recovery of ischemic organs (including the brain) after ischemic injury [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…Although transplantation of neural stem/progenitor cells promotes neural regeneration after brain injury, the survival and functional integration of transplanted cells is severely limited, and a large tissue cavity remains within the injury site. [37][38][39] Combination of ECM with other treatments, for example, transplantation of NSCs, may boost the beneficial effects of either treatment alone. Our previous study demonstrated that transplantation of UBM carrying NSCs significantly reduced TBI lesion and improved long-term sensorimotor and cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%